Trend Analysis of Flipped-Classroom Research in English as A Foreign Language - Agus Hidayat; Septa Aryanika; Mohammad Ridho Kholid; Rohmatillah Rohmatillah; Nur Syamsiah; Nunun Indrasari; Dian Reftyawati (Universitas Pahlawan Tuanku Tambusai, 2022)
The researchers accessed the online Scopus database to gather data for the study. The researchers utilized Microsoft Excel for frequency analysis, VOSviewer for data visualization, and Harzing's Publish or Perish for citation metrics and analysis. According to a keywords search for